2003
DOI: 10.7202/006917ar
|View full text |Cite
|
Sign up to set email alerts
|

Le soutien aux pères de famille biparentale : l’omniprésence de « docteur maman »

Abstract: Les auteures examinent dans cet article les mécanismes de soutien au rôle paternel. Les résultats sont tirés d’entrevues faites auprès de quinze pères de famille biparentale et de onze intervenants. Les deux groupes se prononcent sur la pertinence de différents services pour la population des pères. Le réseau de soutien informel des pères est également exploré. Les résultats révèlent que l’idée qu’ont les intervenants du soutien à offrir aux pères diffère de celle qu’en ont les pères eux-mêmes. L’examen du sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
3
0
6
Order By: Relevance
“…It is also known that fathers' involvement with their children benefits men themselves, enhancing their satisfaction in their marriage 3 and their overall satisfaction in their affective life. 4 Fathers participate more in child care activities when they are supported by their spouse 5 and significant others. 6 Recent research has demonstrated that nurses are considered as significant others for fathers, especially in the perinatal period [7][8] and when children are under five.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that fathers' involvement with their children benefits men themselves, enhancing their satisfaction in their marriage 3 and their overall satisfaction in their affective life. 4 Fathers participate more in child care activities when they are supported by their spouse 5 and significant others. 6 Recent research has demonstrated that nurses are considered as significant others for fathers, especially in the perinatal period [7][8] and when children are under five.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, authors have suggested that fathers and mothers having different socialization processes, they thus require different intervention styles. 5 However health professionals often fail to adapt the support given to fathers to these men's specific needs.…”
Section: Building a Relationship With Fathersmentioning
confidence: 99%
“…Les hommes ont maintenant la possibilité de ressembler à autre chose qu'au père traditionnel, travaillant, rigide et distant; et les attentes des enfants face à leurs pères se modifient de façon radicale (Forget, 2005;Ferland, 2004). Les remises en question du patriarcat et la rupture avec les valeurs traditionnelles 41 se font aussi grâce au mouvement féministe (Devault et Gaudet, 2003). À ce propos, Dulac suggère que :…”
Section: La Révolution Dite « Tranquille »unclassified
“…Selon certains auteurs, une attention égale devrait être portée par les professionnels de la santé envers les pères et les mères (deMontigny et Lacharité, 2002;Devault et Gaudet, 2003). Dans les faits, on remarque que plusieurs, dont les infirmières et les sages-femmes, centrent leur attention sur l'unité mère-bébé plutôt que sur l'ensemble de la famille (Baker, 2007;deMontigny et Lacharité, 2005;Lacharité et collab., 2005;Ménard, 1999).…”
Section: Les Pères Et Les Professionnels De La Santéunclassified